The Blood-Labyrinth Barrier: Non-Invasive Delivery Strategies for Inner Ear Drug Delivery - Zhangyi Yi; Xiaoying Wang; Ge Yin; Yu Sun (Pharmaceutics)
The inner ear is a relatively isolated organ, protected by the blood-labyrinth barrier (BLB). This barrier creates a unique lymphatic fluid environment within the inner ear, maintaining a stable physiological state essential for the mechano-electrical transduction process in the inner ear hair cells while simultaneously restricting most drugs from entering the lymphatic fluid. Under pathological conditions, dysfunction of the stria vascularis and disruption in barrier structure can lead to temporary or permanent hearing impairment. This review describes the structure and function of the BLB, along with recent advancements in modeling and protective studies related to the BLB. The review emphasizes some newly developed non-invasive inner ear drug delivery strategies, including ultrasound therapy assisted by microbubbles, inner ear-targeting peptides, sound therapy, and the route of administration of the cerebrospinal fluid conduit. We argue that some intrinsic properties of the BLB can be strategically utilized for effective inner ear drug delivery.